Eksistensi dan Perkembangan Pesantren di Banten: Perspektif Sejarah Pendidikan Islam - Nufus Tahfidzi; B. Syafuri; Umi Kultsum (Fakultas Tarbiyah IAI Darussalam, 2025)
ABSTRACT This article examines the existence and development of Islamic boarding schools in Banten from the perspective of the history of Islamic education. Islamic boarding schools as traditional Islamic educational institutions play an important role in shaping religious and character-based societies in Indonesia. In Banten, the existence of Islamic boarding schools cannot be separated from the role of the Banten Sultanate since the 16th century as a center for the spread of Islam and science. This study uses a qualitative descriptive approach through library studies of historical and scientific sources. In this study, the researcher used descriptive research with Library Research studies. The results of the study show that Islamic boarding schools in Banten have experienced significant developments from time to time, including the colonial era, independence, to the contemporary era. Islamic boarding schools not only function as educational institutions, but also as centers of preaching, resistance to colonialism, and preservation of local Islamic culture. The transformation of Islamic boarding schools in the modern era shows their flexibility and resilience in facing the challenges of the times without losing their Islamic identity. This article emphasizes the importance of Islamic boarding schools as strategic Islamic educational institutions that are deeply rooted in the history of education in Indonesia.